Rashtriya Barh Ayog (National Commission on Floods) Report Volume-I - Planning Commission (Planning Commission, 1980)
India is a vast country with a total geographical area of 3.29 million sq. km. It lies between the longitude 68°0z and 97°30' east and between latitudes 8°0z and 37°0z north. Due to its vastness, the different regions of the country have varied climates and rainfall patterns. It is, therefore, not uncommon to find one part of the country under the grip of severe floods due to excessive rainfall while another part suffering under the effects of drought. Many a time, it so happens that even in the same State, some areas have excessive rains and consequent floods, while some other areas suffer due to poor rainfall and consequent drought.
Government of India Ministry of Energy and Irrigation (Department of Irrigation)
Government of India Ministry of Energy and Irrigation (Department of Irrigation)